Locally-enhanced optical properties in a hybrid organic/inorganic (coronene/MoS2) Van der Waals heterostructure. (1st March 2023) - Gadelha, Andreij C; Santos, Joyce C C; Rabelo, Cassiano; Vasconcelos, Thiago L; Alencar, Rafael S; Monken, Vitor; Miranda, Hudson L S; Cury, Luiz A; Jaques, Ygor M; Tromer, Raphael M; Galvão, Douglas S; Cançado, Luiz G; et al.
Abstract: Hybrid organic/inorganic Van der Waals heterostructures have emerged recently with enormous potential applications in nanotechnology and industrial areas. In these heterostructures, the interfacial effects can modulate the final properties, creating further possibilities in the design and operation of innovative devices. With this perspective in mind, we report on an experimental investigation of a hybrid organic/inorganic heterostructure of coronene and a few-layers MoS 2 . We observe a local enhancement of MoS 2 optical properties using both far-field and near-field Raman scattering and photoluminescence. Mainly located at MoS 2 edges and defects, the local enhancement is due to the assembling of coronene molecules in MoS 2, as confirmed by atomic force microscopy. Quantum semi-empirical and fully atomistic molecular dynamics simulations were also used to gain further insights into these phenomena. Our results pave the way to engineer molecules in two-dimensional (2D) layered nanomaterials and control and modulate optical phenomena.